Feasibility of Using Green Laser in Monitoring Local Scour around Bridge Pier - Rahul Dev Raju; Sudhagar Nagarajan; Madasamy Arockiasamy; Stephen Castillo (Geomatics, 2022)
Scour around bridge piers is considered as one of the major factors which causes failure of bridges in the United States. An undetected scour can affect the stability of the bridge, eventually leading to the collapse of the bridge. The experimental investigation of scour around a pier using a non-contact measuring method is carried out in this research. A green laser-based non-contact ranging technique is performed on a prefabricated scour hole to study the factors influencing the ability to reconstruct the shape of a scour hole. The experiment was conducted in a 10 ft diameter pool and Leica scan station II was used for the scanning of the scour hole. The turbidity of the water was changed by adding Kaolinite powder to the water. The turbidity was varied from 1.2 NTU to 20.8 NTU by adding Kaolinite. The lab experiments involved changing the turbidity of water to simulate real world conditions. The results from the experimental study show that the turbidity of the water has a direct dependence on the efficiency of the green laser to map the underwater scour profile. The ability of the green laser to capture the fabricated scour hole and pool bed topography were decreased as the turbidity was increased even when the water depth of the pool was reduced. The results from the study show that the green laser is effective in underwater scanning and can be also used for bathymetry profiling and the detection of underwater objects. The method of underwater scanning using a green laser for detecting scour around bridge pier is safe, efficient, and economical.